Factors Affecting the Level of Satisfaction of Doctors Using the YesDok Telemedicine Information System - Handoko, Marshell Timotius; Lahindah, Laura (International Journal of Science and Society, 2024)
Healthcare is one of the most important things in today's society, especially with technology. Indonesia has the fewest doctors in Southeast Asia, at 0.4 doctors per thousand population. This innovation in medical services can help patients and medical personnel to be more efficient and effective. Telemedicine as the practice of using technology to deliver health services remotely. In virtual situations, trust becomes very important in online services. Doctors are the main important part of YesDok telemedicine services and the importance of doctor satisfaction as users of telemedicine information systems is the main target. Quantitative research was conducted on a sample of all YesDok in-house doctors, the data was analyzed with SPSS 25. The results showed a significant effect on the level of satisfaction of doctors using the telemedicine system on the information quality factor and the level of reliability. Showing the main important factors needed by doctors as users of the telemedicine system.